An HLA-Transgenic Mouse Model of Type 1 Diabetes That Incorporates the Reduced but Not Abolished Thymic Insulin Expression Seen in Patients - Jeffrey Babad; Riyasat Ali; Jennifer Schloss; Teresa P. DiLorenzo (Journal of Diabetes Research)
Type 1 diabetes (T1D) is an autoimmune disease characterized by T cell-mediated destruction of the pancreatic islet beta cells. Multiple genetic loci contribute to disease susceptibility in humans, with the most responsible locus being the major histocompatibility complex (MHC). Certain MHC alleles are predisposing, including the common HLA-A∗02:01. After the MHC, the locus conferring the strongest susceptibility to T1D is the regulatory region of the insulin gene, and alleles associated with reduced thymic insulin expression are predisposing. Mice express two insulin genes, Ins1 and Ins2. While both are expressed in beta cells, only Ins2 is expressed in the thymus. We have developed an HLA-A∗02:01-transgenic NOD-based T1D model that is heterozygous for a functional Ins2 gene. These mice exhibit reduced thymic insulin expression and accelerated disease in both genders. Immune cell populations are not grossly altered, and the mice exhibit typical signs of islet autoimmunity, including CD8 T cell responses to beta cell peptides also targeted in HLA-A∗02:01-positive type 1 diabetes patients. This model should find utility as a tool to uncover the mechanisms underlying the association between reduced thymic insulin expression and T1D in humans and aid in preclinical studies to evaluate insulin-targeted immunotherapies for the disease.